2010
DOI: 10.1074/jbc.m109.075648
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of CD45 Lateral Mobility by the Spectrin-Ankyrin Cytoskeleton of T Cells

Abstract: The leukocyte common antigen, CD45, is a critical immune regulator whose activity is modulated by cytoskeletal interactions. Components of the spectrin-ankyrin cytoskeleton have been implicated in the trafficking and signaling of CD45. We have examined the lateral mobility of CD45 in resting and activated T lymphocytes using single-particle tracking and found that the receptor has decreased mobility caused by increased cytoskeletal contacts in activated cells. Experiments with cells that have disrupted ␤⌱ spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 42 publications
1
50
1
Order By: Relevance
“…3D) that interfere with the cytoskeleton and early TCR signaling: stomatin-like protein 2 (STOML2) (32,33), myosin regulatory L chain MRCL3 variant (MRCL3) (34), and the bII-spectrin. bII-Spectrin was described to be involved in CD3 and CD45 surface display and IL-2 production (35,36). We found that CD45 and CD3 surface expression was enhanced in GBP-1-silenced Jurkat T cells, whereas the levels of several other surface receptors such as CD11a, CD18, and CD43 were not altered (Fig.…”
Section: Influence Of Gbp-1 On Cell Spreading and Expression Of Cd3 Amentioning
confidence: 52%
See 2 more Smart Citations
“…3D) that interfere with the cytoskeleton and early TCR signaling: stomatin-like protein 2 (STOML2) (32,33), myosin regulatory L chain MRCL3 variant (MRCL3) (34), and the bII-spectrin. bII-Spectrin was described to be involved in CD3 and CD45 surface display and IL-2 production (35,36). We found that CD45 and CD3 surface expression was enhanced in GBP-1-silenced Jurkat T cells, whereas the levels of several other surface receptors such as CD11a, CD18, and CD43 were not altered (Fig.…”
Section: Influence Of Gbp-1 On Cell Spreading and Expression Of Cd3 Amentioning
confidence: 52%
“…It was described that the bII-spectrin cytoskeleton influences IL-2 production in T cells by mediating CD3 and CD45 surface expression (35,36). We show in this article that GBP-1 interferes with CD3 and CD45 surface display (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…SPT measurements showed that CD45 mobility decreased upon cell activation, and this decrease in mobility was attenuated by disruption of the actin cytoskeleton. Peptide fragments of β1 spectrin were used to show that CD45 utilized spectrin to maintain cytoskeletal linkages with actin and with ankyrin (Cairo et al, 2010). These spectrin–ankyrin and spectrin–actin links stabilized CD45 in the membrane.…”
Section: Membrane Protein Dynamics In Mammalian Cellsmentioning
confidence: 99%
“…A vesicular spectrin-ankyrin adaptor protein trafficking system may mediate the capture and transport of many membrane proteins while cooperating with vesicular target molecules to transport cargo proteins. Recently, Cairo et al [25] used bioinformatics methods to establish a model of the CD45-cytoskeleton interaction and elucidated that the spectrin-ankyrin-actin network significantly controls immunoreceptor mobility.…”
Section: Spectrin-based Functional Complexmentioning
confidence: 99%